Development of refrigerant (R32) flow maldistribution model for microchannel heat exchanger - Chng, Ming Hui (2016)
Conservation of energy becomes a challenging issue in air-conditioning applications.In order to overcome this issue, many researchers have recommended using microchannel heat exchanger and low global warming potential and ozone depletion potential refrigerant, such as R32, in air conditioning systems. However, most of the designers of heat exchanger face a major problem which is the performance deterioration due to tube-side refrigerant maldistribution. It is found that most of the researchers did not quantify the effect of performance deterioration due to refrigerant maldistribution. Besides that, there is no model which is able to investigate the influence of the statistical moments of probability density function on the R32 tubeside flow maldistribution in microchannel heat exchanger. Moreover, there is no researcher developed performance deterioration correlation due to refrigerant tubeside maldistribution. In order to have a comprehensive analysis on tube-side maldistribution in microchannel heat exchangers, it is recommended to quantify the influence of the higher statistical moments of probability density function of the flow maldistribution profiles on the performance degradation. In order to analyze the influence of the higher statistical moments of probability density function of the flow maldistribution profiles on the performance degradation, it is necessary to develop a suitable model which is able to perform the numerical simulation and analyzed refrigerant flow maldistribution. Moreover, a performance deterioration correlation based on refrigerant tube-side maldistribution should be developed in order to reduce the development time of heat exchanger. In order to achieve the goals in this research, a model without sub-cool and superheat and with sub-cool and superheat were developed. Next, the performance degradation of microchannel heat exchanger due to refrigerant tube-side maldistribution was quantified and analyzed. After that,the model considering superheat and sub-cool were validated by doing experiment.Finally, the performance deterioration correlation due to refrigerant maldistribution was being developed. From the numerical simulation, it was found that the performance deterioration factor can up to 1% when the standard deviation was more than 0.3 and the performance deterioration factor can reached 1% for skew below than -0.5. The flow maldistribution profile with high standard deviation and high negative skew have a large impact on the performance deterioration of microchannel heat exchanger and can up to 10%. Furthermore, the performance deterioration factor reached to 4% when the mean was less than 0.9. It was found that the impact of superheat on performance deterioration factor was only 0.1%. Moreover, it was found that the heat transfer performance of microchannel heat exchanger drops significantly when the sub-cool is very high. In conclusion, a maldistribution profile with low standard deviation, high positive skew, high superheat and low sub-cool was preferred in order to minimize the deterioration effect. Finally, the simple form of the performance deterioration correlation equations was developed to allow a quick calculation of the exchanger thermal performance degradation once the flow maldistribution profile was known. The best possible design of microchannel heat exchanger was able to achieve by extract the statistical moments from simulation. The proposed correlation in this research offers a faster and simpler method to analyze the maldistribution problem.